Peningkatan Kualitas Tahu Mbak Trisni Di Kecamatan Percut Sei Tuan - Herbert Sipahutar; Makmur Sirait; Mukti Hamjah Harahap; Irfandi; Deo Demonta Panggabean; Anggriyani; Dedy Husrizal Syah (Universitas Lancang Kuning, 2020)
The business of Tofu Mbak TRISNI located in Percut Sei Tuan has produced about 2 years. The Problems in the partner's efforts are: 1) The partner has not yet had the knowledge and understanding of the quality of clean water and is worthy tobe used for the manufacture of tofu and for other activities, 2) The partner does not have the knowledge and skills About clean water treatment technology of households, 3) The partner requires additional knowledge to cultivate less viable water in order to be a decent water used for the purpose of making tofu and daily necessities and 4) partners need Simple Technology to cultivate water is less feasible to be a decent water used for the purpose of making tofu and household use. The method of implementation of activities carried out by approach method includes extension activities, training, mentoring and workshop on appropriate technology to process water is not worthy of use into viable water tailored to the condition Environment. This PKM activity generates the availability of clean water for the manufacture of tofu that will produce good quality and safe for health for long-term consumption as well as increased knowledge and skills partner in operating the tool TTG For longer periods of time.